Macroeconomic Evolution after a Production Shock: the Role for Financial Intermediation - Dmitri V. Vinogradov (University of Heidelberg, Department of Economics, 2006)
Financial intermediaries may increase economic efficiency through intertemporal risk smoothing. However without an adequate regulation, intermediation may fail to do this. This paper studies the effects of a production shock in a closed economy and compares abilities of market-based and bank-based financial systems in processing the shock. Unregulated banking system may collapse in absence of a proper regulation. The paper studies several types of regulatory interventions, which may improve the performance of the banking system.
Keywords: D50; G21; G28; E44; E53; O16; 330; Financial intermediation; overlapping generations; general equilibrium; intertemporal smoothing; Finanzintermediation; Wirkungsanalyse; Schock; Wirtschaftliche Anpassung; Allgemeines Gleichgewicht; Overlapping Generations; Theorie